After the storm: how to save democracy in Europe (Tielt, 2015)
"In his years as president of the European Council, Herman Van Rompuy met with an impressive series of leading thinkers to discuss the future of Europe. He set the bar high by asking them to tell him something he had not heard before. The philosophers, economists, political scientists and legal experts who took up his invitation met the challenge brilliantly. In openhearted and stimulating discussions, they expressed both fears and hopes for the European project at a point when Europe, with the euro crisis, found itself in a raging storm. At the request of the president, some of these thinkers have now put their ideas and solutions on paper. Herman Van Rompuy has written the introductory essay. The central, topical theme of this collection is the democratic legitimacy of Europe and its institutions. Where one sees too little European democracy, another sees too much Brussels presumption. The euro crisis exposed the tension between democracy and a currency union, and between the nation states of the EU. The nationalist refexes that accompany these tensions are visible today in a new and dangerous storm that is indirectly addressed in the book: the migration crisis. All this makes After the Storm indispensable reading for anyone concerned about Europe."